STRATEGI MARKETING DALAM MENINGKATKAN JUMLAH PELANGGAN: STUDI KASUS TOKO AUSATH GROSIR DARUSSALAM - Agus Alfan Rosyid (Universitas KH. Mukhtar Syafaat, 2025)
The objectives of this study are: 1) To determine how Toko Ausath Grosir Darussalam’s marketing strategies aim to increase the number of customers, 2) To determine the marketing strategies implemented at Toko Ausath Grosir Darussalam based on a SWOT analysis. In conducting the SWOT analysis, the author created an IFAS Matrix (Internal Factor Analysis Summary) and an EFAS Matrix (External Factor Analysis Summary). The IFAS Matrix was compiled based on the strengths and weaknesses of Toko Ausath Grosir Darussalam, while the EFAS Matrix was compiled based on the opportunities and threats facing Toko Ausath Grosir Darussalam. After determining the values of the IFAS and EFAS matrices, the next step is to assess the company’s position based on these values within the IE (Internal-External) matrix. The research findings indicate that the marketing strategies aimed at increasing customer numbers align with Sharia principles. This is evidenced by the annual revenue growth achieved by Ausath Grosir Store. In conclusion, the marketing strategy to increase the number of customers is in accordance with Sharia, both in concept and practice, by adhering to Sharia principles, which include belief in God, family values, trustworthiness, and conducting halal business.